2018
DOI: 10.1515/reveh-2018-0026
|View full text |Cite
|
Sign up to set email alerts
|

Demographic, socio-economic and behavior as risk factors of tuberculosis in Malaysia: a systematic review of the literature

Abstract: Abstract Background Tuberculosis (TB) is making a comeback and has remained one of the main causes of mortality among the list of infectious diseases in Malaysia. Objective To evaluate the burden and demographic, socio-economic and behavior as risk factors of TB among communities in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 36 publications
2
17
0
Order By: Relevance
“…Sociodemography characteristics are considered as risk factors for TB and MDR-TB incidence [ 34 ]. Our results showed that TB cases were higher in men, similar to most studies in Malaysia [ 35 ]. Active TB cases are shown to affect individuals of productive age, as shown in a Java island, Indonesia study [ 35 38 ].…”
Section: Main Textsupporting
confidence: 91%
See 1 more Smart Citation
“…Sociodemography characteristics are considered as risk factors for TB and MDR-TB incidence [ 34 ]. Our results showed that TB cases were higher in men, similar to most studies in Malaysia [ 35 ]. Active TB cases are shown to affect individuals of productive age, as shown in a Java island, Indonesia study [ 35 38 ].…”
Section: Main Textsupporting
confidence: 91%
“…Our results showed that TB cases were higher in men, similar to most studies in Malaysia [ 35 ]. Active TB cases are shown to affect individuals of productive age, as shown in a Java island, Indonesia study [ 35 38 ]. However, we observed 17 patients who were less than 40 years of age and 33 who were more than 40 years old.…”
Section: Main Textsupporting
confidence: 91%
“…All these data were retrieved via MyTB and double checked from TBIS to prevent errors. These variables were selected through the consideration of the real situation in Malaysia from the references of previous literatures [ 56 , 57 ]. Other data such as individual’s ID, type of TB (smear positive, smear negative, extrapulmonary, drug-resistant), and date of diagnosis (month, year) were also collected.…”
Section: Methodsmentioning
confidence: 99%
“…The TB incidence was positively associated with the temperature, precipitation, and wind speed (all P-values < 0.05) (Moosazadeh, Khanjani and Parsaee, 2015). The risk factors for the development of TB, specifically in a high-risk population, should be targeted through the implementation of specialized interventions (Mohidem et al, 2018).…”
Section: Contact With Patientsmentioning
confidence: 99%